European economic legal order after Brexit : markets and institutions. - Cardi, E. (Enzo) ([S.l.] : Routledge, 2021)
This book takes an innovative approach to provide a mirror perspective of the legal systems of the UK and the EU in contemporary institutional scenarios. At the beginning of the second decade of the 21st century, the legal systems of the EU and the UK are facing challenges of epic proportions. Never before have the two legal orders been confronted with the simultaneous impact of a series of events. First, the effect of the divorce between the two regulatory systems caused by the UK's withdrawal from the EU. The Negotiating Documents and the Draft Texts being discussed and aimed at leading to a `New Partnership' are examined in the book. Second, the book discusses the impact of the coronavirus shock in all European economies leading to a substantial change of political perspective in the EU legal order implying innovative debt instruments. Third, it explores the consequences of the judicial activism of the German Constitutional Court undermining the strategic role of the European Central Bank and the primacy of the European Union Court of Justice. The book questions the effects deriving from the legacy, i.e. the foundations of the two legal systems, on handling the issues of our time, the impact on market regulation of the striking contemporary events and the unsettled consequences on policy of the current convulsing political and financial landscape. The book will be essential reading for those working in the areas of European public regulatory law.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Economics / Comparative; LAW / General; LAW / Administrative Law & Regulatory Practice; European Union -- Great Britain; Administrative law -- Europe; Administrative law -- Great Britain